Race, Neighborhood Danger, and Coping Strategies Among Female Probationers and Parolees. (January 2014) - Cobbina, Jennifer E.; Morash, Merry; Kashy, Deborah A.; Smith, Sandi W.
Research suggests that individuals on probation and parole typically reside in impoverished neighborhoods affected by multiple forms of socioeconomic disadvantage. These neighborhoods are often extremely segregated, resulting in the concentration of deleterious effects, including crime, on communities of color, especially African Americans. We build on previous research by examining how Black and White female offenders negotiate neighborhood crime in distressed communities. Using a mixed-methods approach, our findings suggest that perceptions of neighborhood safety, crime, and strategies to avoid offending are different for Black and White women and related to neighborhood context. We propose that future research should investigate long-term outcomes of the use of particular strategies to address neighborhood crime.